Music Intervention Approaches for Alzheimer’s Disease: A Review of the Literature - Leggieri, Melissa; Thaut, Michael H.; Fornazzari, Luis; Schweizer, Tom A.; Barfett, Joseph; Munoz, David G.; Fischer, Corinne E. (Frontiers in Neuroscience, 2019)
Music interventions have been widely adopted as a potential non-pharmacological therapy for patients with Alzheimer’s disease (AD) to treat cognitive and/or behavioural symptoms of the disease. In spite of the prevalence of such therapies, evidence for their effectiveness report mixed results in the literature. The purpose of this narrative review is to investigate the effectiveness of various intervention strategies (music therapy versus music listening techniques) and music type used in the intervention (individualized versus non-individualized music) on cognitive and behavioural outcomes for persons with AD. Databases were searched for studies using either active music therapy or music listening techniques over the last ten years. These studies were in English, included persons with AD dementia, and whose protocol gathered pre- and post-intervention outcome measures. We initially identified 206 papers which were then reduced to 167 after removing duplicates. Further review yielded 13 papers which were extensively reviewed, resulting in a final sample of six papers. Our analysis of these papers suggested that, regardless of the music intervention approach, individualized music regimens provided the best outcomes for the patient. Furthermore, music listening may act as a relaxation technique and therefore provide a long-term impact for the patient, while active music therapy may acts to engage participants through social interaction and provide acute benefits. Our findings suggest that music techniques can be utilized in various ways to improve behavior and cognition.